1995
DOI: 10.1007/bf00301604
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound bone measurement in pediatric subjects

Abstract: Ultrasound bone measurement in healthy (n = 71) and osteopenic (n = 18) children aged 6 through 13 years of both sexes has been evaluated using the Achilles densitometer (Lunar Corporation). Measurements on the os calcis included speed of sound (SOS), broadband ultrasound attenuation (BUA), and a calculated "stiffness" index. The Achilles was adapted for children by a special positioning procedure that included the use of foot shims, and beam collimation on the receiving transducer. The precision of ultrasound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
74
4
2

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(87 citation statements)
references
References 24 publications
7
74
4
2
Order By: Relevance
“…3(b) and Table 3. The stiffness increase with age as predicted in Table 3 agrees well with that observed in in-vivo ultrasound experiments on the os calcis bones of children aged 6 through 13 years [38].…”
Section: Micromechanics-derived Bone Matrix Stiffness In Adults and Csupporting
confidence: 85%
“…3(b) and Table 3. The stiffness increase with age as predicted in Table 3 agrees well with that observed in in-vivo ultrasound experiments on the os calcis bones of children aged 6 through 13 years [38].…”
Section: Micromechanics-derived Bone Matrix Stiffness In Adults and Csupporting
confidence: 85%
“…Both feet were measured twice in the same session (right, left, right, left), and the mean was used for statistical analyses. The precision data for QUS in children have been reported as 0.2% for SOS, 1.5% for BUA, and 1.8% for stiffness (13).…”
Section: Qualitative Ultrasoundmentioning
confidence: 99%
“…The pathological meaning of these values still needs to be evaluated. Only one study investigated SI values in children with bone disorders: Jaworski et al 27 observed a mean SI of 50.6 ± 13.7 in eighteen 6-to 13-year old children having osteopenia. According to these findings, our reference values for 5.5-9.5-year-old girls in the 1st age-specific SI percentile (range: 49.9-64.9) are close to this pathological value for osteopenia.…”
Section: S79mentioning
confidence: 99%
“…24 Besides the difference between QUS and DXA measurements assessing bone status, bone stiffness showed good correlations with aBMD assessed by DXA in adults 25 and children. 26,27 Furthermore, it revealed to be highly prognostic with regard to bone fractures in adults 28 and proved to be a valid measure for the risk for osteopenia in young patients. 27 Up to now, QUS references were established mainly for adults but are barely available for children and adolescents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation